PENERAPAN METODE GIVING QUESTIONS AND GETTING ANSWERS PADA PEMBELAJARAN MENULIS NARASI BAHASA INDONESIA KELAS IV UPTD SDN 3 CANGKO TAHUN AJARAN 2022/2023 - Farihiyah; Ade Sumini Septiyanti (JOURNAL SAINS STUDENT RESEARCH, 2023)
The background to this research is the low quality of learning outcomes for class IV students at UPTD SDN 3 Cangko regarding the material for writing Indonesian narrative texts. Thematic is a subject that emphasizes students to find out and discover their own knowledge. Activities in thematic learning at UPTD SDN 3 Cangko are dominated by teachers, students tend to be passive, teachers do not involve students so that students' understanding is less than satisfactory. This classroom action research aims to improve student learning outcomes. One alternative that can be used is to apply a learning method that helps students' activity and creativity, namely the Giving Questions and Getting Answers method. This research is classroom action research (PTK). The subjects of this research were 10 students in class IV UPTD SDN 3 Cangko. The object of the research is the application of the Giving Questions and Getting Answers method to improve student learning outcomes in learning to write Indonesian narratives in class IV. This research consisted of 2 cycles. Research data obtained from observations during learning and documentation activities. The data analysis technique used is the qualitative description method. Meanwhile, to calculate the results using quantitative methods. Student learning outcomes in pre-cycle learning reached an average score of 57, while cycle 1 test results achieved an average score of 70.2 from pre-cycle. As for cycle two, students achieved an average score of 75.6.